PREVALENCE OF DYSLIPIDEMIA AND THE ASSOCIATION WITH LEVELS OF TSH AND T4 HORMONES AMONG PATIENTS IN SOUTH REGION OF JORDAN - Atrooz, Omar; Hiresh, Mazen; Alghonmeen, Reham; Atrooz, Mohammad; Hiresh, Ghofran; Alasoufi, Aseel; Atrooz, Ihssan (Journal of Medical Biochemistry, 2023)
Background: Elevated levels of glycolipid profile components and blood glucose are world population problems. Whereas the dysglycolipidemia is characterized by dyslipidemia and elevated levels of fasting blood sugar (FBS) and HbA1C. Therefore, our aim of this cross-sectional study is to estimate the prevalence of dysglycolipidemia and the existence of association of TSH and T4 and glycolipid profiles. Methods: Cross-sectional data were obtained from the medical laboratory of Ma’an Governmental Hospital. A total of 141 patients’ results were collected (18-60 years). Differences in the glycolipidemic profiles according to age and sex and TSH and FT4 were compared. Different statistical analyses were used to analyze the prevalence of dysglycolipidemia and the correlation with the levels of TSH and FT4. Results: The study involved results of 141 patients (54.7% males and 45.3% females) in Ma’an Province (Jordan), who visited the internal medicine clinic at Ma’an Governmental Hospital. Patients have a heavyweight and BMI of more than 25 Kg/m2. The overall results of the prevalence of dyslipidemia indicated that patients have 42.5% of hypercholesterolemia, 48.2% of high LDL-C, 34.1% of hypertriglyceridemia, and 41.8% of low HDL-C. The prevalence of isolated lipid profiles showed that 10 patients have mixed dyslipidemia. The association of dyslipidemia with age indicated a positive significance between triglyceride and older people (≥40 years), while HDL levels have a significance with gender (p=0.025). The overall ANOVA model yielded non-statistical significant results between levels of any components of lipid profile and levels of TSH and T4 hormones. Welch test (p=0.036) showed positive significance between levels of blood glucose and triglyceride levels. Conclusion: Our results showed and confirmed the presence of a high percentage of hyperlipidemia in Ma’an province and there was no relationship with levels of TSH and T4. A relationship exists between levels of triglycerides and blood glucose concentrations.